2019
DOI: 10.1097/md.0000000000014663
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased B7 protein expression by infiltrating immune cells with progression of gastric carcinogenesis

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…In addition, we found that there was a significant correlation between B7-H3 and CD68 expression. This result is consistent with our previous findings (24), and our group also found that B7-H3 regulates the differentiation of tumor-associated macrophages in human colorectal carcinoma (43). However, the correlation between B7-H3 and CD31 or α-SMA expression was much higher than that of B7-H3 and CD68 expression, suggesting that B7-H3 may play a vital role in the tumor microenvironment, including endothelial cells and fibroblasts.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, we found that there was a significant correlation between B7-H3 and CD68 expression. This result is consistent with our previous findings (24), and our group also found that B7-H3 regulates the differentiation of tumor-associated macrophages in human colorectal carcinoma (43). However, the correlation between B7-H3 and CD31 or α-SMA expression was much higher than that of B7-H3 and CD68 expression, suggesting that B7-H3 may play a vital role in the tumor microenvironment, including endothelial cells and fibroblasts.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with these findings, our study indicated that patients with a higher expression of B7-H3 had significantly poorer overall survival. The expression of B7-H3 in tumor/parenchymal cells was more strongly correlated with CD8-positive and CD68positive cell infiltration and was markedly enhanced at the stages of neoplasia and GAC (24). The function of B7-H3 in promoting gastric cancer development has been studied in depth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B7-H4 is a costimulatory membrane receptor expressed on APCs and cancer cells, interacting with the CD28 ligand and receptors on T lymphocytes causing an inhibitory effect. It has been associated with gastric carcinomas [137], breast cancer [138,139], non-metastatic clear cell renal cell carcinoma [140] and glioblastoma [141], among other tumor types. Its loss was also recently associated with the development of autoimmune diabetes [142].…”
Section: Immunotherapeutic Approaches Against Cancermentioning
confidence: 99%